The laparoscopic banded gastric bypass – operation technique - Simon Küsters; Goran Marjanovic; Tobias Baumann; Philipp Holzner; Wojciech K. Karcz (Videosurgery and Other Miniinvasive Techniques)
The banded Roux-en-Y gastric bypass can be used as a primary or revisionary bariatric procedure. This article describesthe operation technique including materials, size and placement of the banding and gives an overview con cerningevolution and indications of the operation. A video of a primary banded Roux-en-Y gastric bypass is presented.